2015
DOI: 10.18632/oncotarget.2902
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar ATPase ‘a2’ isoform exhibits distinct cell surface accumulation and modulates matrix metalloproteinase activity in ovarian cancer

Abstract: Tumor associated vacuolar H+-ATPases (V-ATPases) are multi-subunit proton pumps that acidify tumor microenvironment, thereby promoting tumor invasion. Subunit ‘a’ of its V0 domain is the major pH sensing unit that additionally controls sub-cellular targeting of V-ATPase and exists in four different isoforms. Our study reports an elevated expression of the V-ATPase-V0a2 isoform in ovarian cancer(OVCA) tissues and cell lines(A2780, SKOV-3 and TOV-112D). Among all V0’a’ isoforms, V0a2 exhibited abundant expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 50 publications
5
72
0
Order By: Relevance
“…Subsequent work demonstrated that the V-ATPase is present on the plasma membrane of invasive breast cancer cells, but not noninvasive breast cancer cells, and participates in control of cytoplasmic pH (175). The V-ATPase has since been found to be expressed on the plasma membranes of numerous invasive cancer cell types, including melanoma, Ewing sarcoma, and breast, liver, lung, ovarian, esophageal, prostate, and pancreatic cancers (9,21,23,24,63,71,90,107,125,136,176,216). Furthermore, overexpression of particular V-ATPase subunits has been observed in both human cancer cell lines and human tumor samples.…”
Section: A Expression and Localization Of V-atpases In Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work demonstrated that the V-ATPase is present on the plasma membrane of invasive breast cancer cells, but not noninvasive breast cancer cells, and participates in control of cytoplasmic pH (175). The V-ATPase has since been found to be expressed on the plasma membranes of numerous invasive cancer cell types, including melanoma, Ewing sarcoma, and breast, liver, lung, ovarian, esophageal, prostate, and pancreatic cancers (9,21,23,24,63,71,90,107,125,136,176,216). Furthermore, overexpression of particular V-ATPase subunits has been observed in both human cancer cell lines and human tumor samples.…”
Section: A Expression and Localization Of V-atpases In Tumor Cellsmentioning
confidence: 99%
“…Similar results have been obtained with other cancer cell types. The invasion and migration of pancreatic cancer cells are reduced upon treatment with concanamycin A (23), and V-ATPase inhibition decreases in vitro invasion of prostate cancer cells and migration of ovarian cancer cells (90,125). Finally, knockdown of subunit c of V 0 and subunit A of V 1 using siRNA treatment, which results in complete ablation of V-ATPase activity, reduces the invasiveness of liver and gastric cancer cells, respectively (101,108,216).…”
Section: B V-atpases Are Important For Tumor Cell Invasion and Migramentioning
confidence: 99%
“…Other studies have described expression of V‐ATPase/specific subunits in pancreatic cancer,32, 33 nonsmall cell lung cancer,34 oral squamous cell carcinoma,35, 36 ovarian cancer,37 cervical cancer,38 breast cancer,39, 40 gliomas,41 and hepatocellular carcinoma 42. A summary of studies investigating clinical significance of V‐ATPase in cancer is provided in Table 1.…”
Section: Dysregulation Of V‐atpase In Cancermentioning
confidence: 99%
“…Increased cancer cell invasive activity is frequently associated with aberrant V‐ATPase plasma membrane localization suggesting that increased acidification of the extracellular space plays an important role 29, 33, 34, 37, 47, 48, 49, 50, 51, 52…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation